2005
DOI: 10.1086/426915
|View full text |Cite
|
Sign up to set email alerts
|

The Cosmic Evolution of Hard X-Ray-selected Active Galactic Nuclei

Abstract: We use highly spectroscopically complete deep and wide-area Chandra surveys to determine the cosmic evolution of hard X-ray-selected active galactic nuclei (AGNs). For the deep fields, we supplement the spectroscopic redshifts with photometric redshifts to assess where the unidentified sources are likely to lie. We find that the median redshifts are fairly constant with X-ray flux at z $ 1.We classify the optical spectra and measure the FWHM line widths. Most of the broad-line AGNs show essentially no visible … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

102
708
10

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 417 publications
(820 citation statements)
references
References 104 publications
(215 reference statements)
102
708
10
Order By: Relevance
“…The relative HXLFs of the total and the broad-line AGNs from Barger et al (2005) reproduce the results of Steffen et al (2003), who showed that the dominant population at these higher X-ray luminosities, where the redshift identifications are very complete, is broad-line AGNs, while at the lower X-ray luminosities, the non-broad-line AGNs dominate (hereafter, I refer to this as the Steffen effect). Since broad-line AGNs are 466 A. J. Barger straightforward to identify spectroscopically, and the bulk of the X-ray sources at these luminosities have now been observed, one does not need to worry that broad-line AGNs are making up a substantial fraction of the unidentified population.…”
Section: Evolution Of the Hard X-ray Luminosity Functionsupporting
confidence: 67%
See 4 more Smart Citations
“…The relative HXLFs of the total and the broad-line AGNs from Barger et al (2005) reproduce the results of Steffen et al (2003), who showed that the dominant population at these higher X-ray luminosities, where the redshift identifications are very complete, is broad-line AGNs, while at the lower X-ray luminosities, the non-broad-line AGNs dominate (hereafter, I refer to this as the Steffen effect). Since broad-line AGNs are 466 A. J. Barger straightforward to identify spectroscopically, and the bulk of the X-ray sources at these luminosities have now been observed, one does not need to worry that broad-line AGNs are making up a substantial fraction of the unidentified population.…”
Section: Evolution Of the Hard X-ray Luminosity Functionsupporting
confidence: 67%
“…The observation that there are almost no low X-ray luminosity, broad-line AGNs is not a galaxy dilution effect, ruling out the simple unified model. The Barger et al (2005) hard X-ray luminosity function determinations of the supermassive black hole mass densities are a factor of almost two lower than what Yu & Tremaine (2002) found due to the Yu & Tremaine extrapolation of the optical QSO luminosity function outside the optically observed luminosity range. Comparing this result with the local 470 A. J. Barger supermassive black hole mass density, there is now room for obscured accretion by the optically-narrow AGNs.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations